Solutions to quasilinear equations of $N$-biharmonic type with degenerate coercivity - Sami Aouaoui (Electronic Journal of Differential Equations, 2014)
In this article we show the existence of multiple solutions for quasilinear equations in divergence form with degenerate coercivity. Our strategy is to combine a variational method and an iterative technique to obtain the solutions.